2017
DOI: 10.1159/000456598
|View full text |Cite
|
Sign up to set email alerts
|

A New Perspective for Osteosarcoma Therapy: Proteasome Inhibition by MLN9708/2238 Successfully Induces Apoptosis and Cell Cycle Arrest and Attenuates the Invasion Ability of Osteosarcoma Cells in Vitro

Abstract: Background: The proteasome exists in all eukaryotic cells and provides the main route of intracellular proteins degradation involved in cell growth and apoptosis. Proteasome inhibition could block protein degradation pathways and disturb regulatory networks, possibly leading to profound effects on cell growth, particularly in cancer cells. A proteasome inhibitor with an appropriate toxicity index for malignant cells rather than normal cells would be an attractive anticancer therapy. Methods: The human osteosar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…This result suggests that calcium channels that experienced long-duration overloading remained open on the cell membrane, which led to excessive intracellular calcium. Opening of the PTP channel on mitochondria is irreversible, the cytochrome C located in the mitochondrial membrane is released into the cytoplasm, and the gene and protein expression of Caspase-9 and Caspase-3 induces cell apoptosis [50-51]. Therefore, one of the main factors causing cell apoptosis under overloading is the opening of calcium channels on the membrane rather than the release of ATP.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that calcium channels that experienced long-duration overloading remained open on the cell membrane, which led to excessive intracellular calcium. Opening of the PTP channel on mitochondria is irreversible, the cytochrome C located in the mitochondrial membrane is released into the cytoplasm, and the gene and protein expression of Caspase-9 and Caspase-3 induces cell apoptosis [50-51]. Therefore, one of the main factors causing cell apoptosis under overloading is the opening of calcium channels on the membrane rather than the release of ATP.…”
Section: Discussionmentioning
confidence: 99%
“…Annexin V-FITC/PI double staining was used to confirm the apoptotic effect on cells, and the samples were analyzed by a flow cytometer (Becton Dickinson) using FACSDiva TM software [26]. …”
Section: Methodsmentioning
confidence: 99%
“…Surgery combined with adjuvant chemotherapy is currently the standard treatment for osteosarcoma (1). In recent years, although a great deal of effort has been made toward improving chemotherapy regimens, the overall prognosis remains poor and much of this may be attributed to drug resistance (2). P-glycoprotein (P-gp), an ATP-binding cassette (ABC) membrane transporter encoded by multidrug resistance 1 (MDR1), is commonly located at the plasma membrane and functions as an ATP-dependent efflux pump for diverse naturally occurring hydrophobic anticancer drugs, including Adriamycin (ADR) (3).…”
Section: Introductionmentioning
confidence: 99%
“…The functions of parenchymal VASH1 in tumor development have drawn more and more attention, but relevant reports remain limited. Liu et al (2) reported that overexpression of VASH1 in colon cancer cells was able to induce apoptosis and senescence, and inhibited cancer cell growth and colony formation in vitro and tumor growth in vivo. In addition, knockdown of VASH1 in cancer cells was able to promote cell growth, adhesion and migration in vitro and enhance tumorigenesis and metastasis in vivo (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation